Optimization Of The Water Distribution Network of Regional Water Utility Company (PDAM) Using Prim Algorithm - Nurviana, Nurviana; Harahap, Jahrohani; Muliani, Fitra (Pattimura International Journal of Mathematics (PIJMath), 2024)
Graph Theory is an old part of mathematics but has many applications. Graphs are used to represent discrete objects and the relationships between them. One of its applications is in the field of network optimization to find the minimum total pipe length. This research will implement Prim algorithm in optimizing the water distribution network of PDAM Tirta Keumueneng Langsa City with the help of the MATLAB software program. The data used is in the form of secondary data, namely a map image of the water distribution network area and the length of the pipe used in PDAM Tirta Keumueng Langsa City. Based on this data, it can be represented as a graph, which can then be obtained a minimum spanning tree using Prim algorithm with the help of the MATLAB software program. The results showed that the minimum total length of pipe produced by Prim’s algorithm was 105.080,8 meters. This means that it can be said that the application of the Prim algorithm provides an optimal total pipe length, thereby saving 10.113 meters of PDAM water distribution network pipes from the initial total length of 115.193,8 meters.